The Influence of Augmented Reality Experience on Customer Loyalty - Paru, Maria Prisila; Rufaidah, Popy (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
Indonesian online customers identified as lacking loyalty. A company should be able to invest in certain aspects to cultivate customer loyalty. This study explored the influence of Augmented Reality (AR) experience on customer loyalty. Specifically, we focus on the context of the AR makeup feature experience. We examined whether each dimension of the AR experience influences customer loyalty. The four dimensions of AR experience applied in this study were environmental embedding, perceived enjoyment, interactivity, and telepresence. This study applied a quantitative approach and employed the non-probability convenience sampling technique (273 respondents). Partial Least Square – Structural Equation Modelling (PLS-SEM) using SmartPLS 4 was utilized for path analysis and hypothesis testing. The model's explanatory power was measured by the R-square and was categorized as moderate (continuance intention R2=0.643 and WOM R2=0.605). The model demonstrated large predictive accuracy, as indicated by a Q2 value (WOM= 0.590 and a ZCI= 0.63). Our findings confirmed that each dimension of the AR experience positively influences customer loyalty, reflected in continuance intention and WOM. Keywords: Augmented reality experience; Environmental embedding, Perceived enjoyment, Interactivity, Customer loyalty